Investigate the Effect of Different Kinds of Discontinuous Fibers on the Mechanical Properties of Epoxy Matrix Composite Materials - Ahmed Muhammad; Ibrahim Atiyah; Hamza Kamal; Ahmed Al-Mukhtar (Engineering and Technology Journal, 2018)
The composite manufacturing has been a wide variety of applications. The low density, stiffness, and weight to strength ratio giving these materials significant mechanical properties in aerospace, and automotive industries. In this work, the specimens of fiber reinforced composites have been prepared by adding different percentage of two types of fibers in epoxy resins matrix. So, the aim of this study is to evaluate the effect of additives on the mechanical properties according to Standard Test Method for Tensile Properties ASTM D3039. The tensile and hardness testing show that the carbon fibers improve the hardness and tensile strength due to their higher mechanical properties. In addition, they have high strength to weight ratio as compare with polypropylene fibers.